SELF-EFFICACY AND CONTROLLABILITY AS WHISTLEBLOWING INTENTION PREDICTORS OF FINANCIAL MANAGERS IN EDUCATIONAL INSTITUTIONS - Natawibawa, I Wayan Yeremia; Irianto, Gugus; Roekhudin, Roekhudin (Badan Pemeriksa Keuangan Republik Indonesia, 2018)
Whistleblowing policy is considered as an effective technique in an investigation audit that is useful for the organization to avoid losses due to fraud. However, employees who intend to report fraud encounter ethical dilemma. Whistleblowing is a behavior that respects honesty, but is also a beha-vior that can possibly compromise organizational loyalty. The objective of this research is to analyze factors influencing whistleblowing intention of financial managers in school organization by understanding the action based on decomposed theory of planned behavior (DTPB). Data were collected through questionnaires that were distributed to financial managers of school organizations, particularly principals, vice-principals, administration heads, treasurers, and financial administration employees of public senior high schools, vocational high schools, and Islamic high schools in Malang City. Research population comprised of 214 persons. Response rate was 89.72%, or there were 192 questionnaires that were duly completed. The analysis method employed was multiple regression. Two independent variables were observed in this research, namely self-efficacy and controllability, while only one dependent variable was examined, namely whistleblowing intention. Result of the research shows that self-efficacy and controllability have positive effect on whistleblowing intention, entailing that whistleblowing intention of employees will increase when they possess self-confidence and strong intention to conduct whistleblowing.